Mobility of primary health care workers in China - Jing Limei; Yuan Jing; Meng Qingyue; Zhang Junhua (BMC, 2009)
Abstract Background Rural township health centres and urban community health centres play a crucial role in the delivery of primary health care in China. Over the past two-and-a-half decades, these health institutions have not been as well developed as high-level hospitals. The limited availability and low qualifications of human resources in health are among the main challenges facing lower-level health facilities. This paper aims to analyse the mobility of health workers in township and community health centres. Methods Data used in this paper come from a nationwide survey of health facilities in 2006. Ten provinces in different locations and of varying levels of economic development were selected. From these provinces, 119 rural township health centres and 89 urban community health centres were selected to participate in a questionnaire survey. Thirty key informants were selected from these health facilities to be interviewed. Results In 2005, 8.1% and 8.9% of health workers left township and community health centres, respectively. The health workers in rural township health centres had three to 13 years of work experience and typically had received a formal medical education. The majority of the mobile health workers moved to higher-level health facilities; very few moved to other rural township health centres. The rates of workers leaving township and community health centres increased between 2000 and 2005, with the main reasons for leaving being low salaries, limited opportunities for professional development and poor living conditions. Conclusion In China, primary health workers in township health centres and community health centres move to higher-level facilities due to low salaries, limited opportunities for promotion and poor living conditions. The government already has policies in place to counteract this migration, but it must step up enforcement if rural township health centres and urban community centres are to retain health professionals and recruit qualified health workers.